Genetic diversity and signatures of selection of drug resistance in Plasmodium populations from both human and mosquito hosts in continental Equatorial Guinea - Mendes, C.; salgueiro, P.; Gonzalez, V.; Berzosa, P.; Benito, A.; Do Rosário, V.E.; De Sousa, B.; Cano, J.; Arez, A.P. (Malaria Journal, 2013)
Background In Plasmodium, the high level of genetic diversity and the interactions established by co-infecting parasite populations within the same host may be a source of selection on pathogen virulence and drug resistance. As different patterns have already been described in humans and mosquitoes, parasite diversity and population structure should be studied in both hosts to properly assess their effects on infection and transmission dynamics. This study aimed to characterize the circulating populations of Plasmodium spp and Plasmodium falciparum from a combined set of human blood and mosquito samples gathered in mainland Equatorial Guinea. Further, the origin and evolution of anti-malarial resistance in this area, where malaria remains a major public health problem were traced. Methods Plasmodium species infecting humans and mosquitoes were identified by nested-PCR of chelex-extracted DNA from dried blood spot samples and mosquitoes. Analysis of Pfmsp2 gene, anti-malarial-resistance associated genes, Pfdhps, Pfdhfr, Pfcrt and Pfmdr1, neutral microsatellites (STR) loci and Pfdhfr and Pfdhps flanking STR was undertaken to evaluate P. falciparum diversity. Results Prevalence of infection remains high in mainland Equatorial Guinea. No differences in parasite formula or significant genetic differentiation were seen in the parasite populations in both human and mosquito samples. Point mutations in all genes associated with anti-malarial resistance were highly prevalent. A high prevalence was observed for the Pfdhfr triple mutant in particular, associated with pyrimethamine resistance. Analysis of Pfdhps and Pfdhfr flanking STR revealed a decrease in the genetic diversity. This finding along with multiple independent introductions of Pfdhps mutant haplotypes suggest a soft selective sweep and an increased differentiation at Pfdhfr flanking microsatellites hints a model of positive directional selection for this gene. Conclusions Chloroquine is no longer recommended for malaria treatment in Equatorial Guinea but sulphadoxine-pyrimethamine (SP) remains in use in combination with artesunate and is the only drug recommended in preventive chemotherapy in pregnancy. The high prevalence of point mutations in Pfdhfr and Pfdhps points to the danger of an eventual reduction in the efficacy of SP combined therapy in P. falciparum populations in Equatorial Guinea and to the essential continuous monitoring of these two genes.